South Sudan : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of South Sudan. (IMF Staff Country Reports; Country Report, 2019)
This 2019 Article IV Consultation discusses that while the peace agreement signed in September 2018 has improved the prospects for lasting peace in South Sudan, the implementation of the agreement has become more protracted than envisaged with the recently announced six-month delay in forming a new national unity government. A relapse into war in mid-2016 spread insecurity across the country and severely affected all economic activities and exacerbated the humanitarian crisis and food insecurity. The country is in a serious economic crisis. The discussions focused on the urgent need to restore macroeconomic stability and rebuild economic buffers. Addressing the macroeconomic imbalance, supported by improvements in oil management and public financial management, is an important factor to rebuild confidence in government policies. This will be necessary to regain access to external financial support from development partners. One of the key policy recommendations is to strengthen oil management and transparency by an immediate stop of contracting new oil-backed advances.